Effect of Shear Center for Different sections for Improving Rigidity of Lathe Bed - Madhu P., Dr. Shailesh Rao A. (International Journal of Advanced Science and Technology, 2020)
In the design of any structural member the shear center location is of greater significance for rigidity improvement. In this direction, the determination of geometrical properties of closed cross sectional areas is often necessary in structural analysis.In this work, rectangular, circular and triangular sections used in lathe beds are modified with their geometry and the corresponding shear centerlocations are found out.The analytical calculation for the location of shear center of rectangular and triangular cross sections is carried out. The analytical calculations for the semicircular section are not carried out due to complexity in its curvature. Further, the finite element analysis of all cross-sections were carried out to determine the location of shear center and validated with the analytical approach.  Thestatic deflection for different sections of the lathe bed model is determined by Finite element analysis using ANSYS software.Improvement in the lathe bed rigidity is seen using the shear center method. In case of triangular and rectangular sections, the location of shear centeris far away from the tool point position and hence more deflection in the lathe bed model is seen. An optimum section is found to be semicircular section, where the deflection is reduced during static loading.Finally, it can be concluded that the shear center method can be adopted by modifying the geometry of the sections to improve the stability of the machine during its operation.